Fracture resistance of fiber-reinforced composite and zirconia all-ceramic systems for posterior partial dentures - Omati Shabestari GH; Haj Mir Agha H; Shahabi S; Bagherpor R (Tehran University of Medical Sciences, 2010)
"nBackground and Aims: Metal-free and fiber-reinforced composite (FRC) restorations have drawn considerable attention and interest in recent years for restoring in the posterior area due to their improved esthetics. Fracture resistance is one of the most important mechanical properties of materials because of 500-600 N load of occlusion. The restorations should tolerate this load. The purpose of this in vitro study was to compare the fracture resistance of FRC with that of zirconia all-ceramic for posterior partial dentures. "nMaterials and Methods: Forty extracted human intact teeth (20 first premolars and 20 first molars) selected for fabricating 10 pairs of fiber-reinforced composite and 10 pairs of zirconia all-ceramic bridges. After receiving standard tooth preparation, the teeth were mounted with 7.5 mm distance between each other. The bridges were made and cemented on the teeth. Then the restorations were stored in 37ºC water for 30 days. The fracture resistance was measured using mechanical testing machine with cross-head speed of 1mm/min. Data were evaluated by Independent Sample T test. "nResults: The mean fracture resistance in the ceramic group was 1329.41 N and for the F.R.C group was 1118.528 N with significant differences between them (P=0.034). The failure modes were mainly cohesive at pontic area for ceramic samples, but adhesive for FRC samples at pontic area. "nConclusion: Both systems showed sufficient fracture resistance for using in posterior area.